Calcium-Dependent Src Phosphorylation and Reactive Oxygen Species Generation Are Implicated in the Activation of Human Platelet Induced by Thromboxane A2 Analogs - Minuz, Pietro; Meneguzzi, Alessandra; Fumagalli, Laura; Degan, Maurizio; Calabria, Stefano; Ferraro, Roberta; Ricci, Marco; Veneri, Dino; Berton, Giorgio (Frontiers in Pharmacology, 2018)
The thromboxane (TX) A2 elicits TP-dependent different platelet responses. Low amounts activate Src kinases and the Rho-Rho kinase pathway independently of integrin αIIbβ3 and ADP secretion and synergize with epinephrine to induce aggregation. Aim of the present study was to investigate the role Src kinases and the interplay with calcium signals in ROS generation in the activatory pathways engaged by TXA2 in human platelets. All the experiments were performed in vitro or ex vivo. Washed platelets were stimulated with 50-1000 nM U46619 and/or 10 µM epinephrine in the presence of acetylsalicylic acid and the ADP scavenger apyrase. The effects of the ROS scavenger EUK-134, NADPH oxidase (NOX) inhibitor apocynin, Src kinase inhibitor PP2 and calcium chelator BAPTA were tested. Spectrofluorimetry was used to measure intracellular calcium and ROS. Born aggregometry, flow-cytometry and western blot analysis were used. Platelet rich plasma from patients treated with dasatinib was used to confirm the data obtained in vitro. We observed that 50 nM U46619 plus epinephrine increase intracellular calcium similarly to 1000 nM U46619. ROS generation was blunted by the NOX inhibitor apocynin. BAPTA inhibited ROS generation in resting and activated platelets. Phosphorylation of Src and MLC proteins were not significantly affected by antioxidants agents. BAPTA and antioxidants reduced P-Selectin expression, activation of integrin αIIbβ3and platelet aggregation. TXA2-induced increase in intracellular calcium is required for Src phosphorylation and ROS generation. NADPH oxidase is the source of ROS in TX stimulated platelets. The proposed model helps explain why an incomplete inhibition of TP receptor results in residual platelet activation, and define new targets for antiplatelet treatment.